Using Short Stories to Teach Language Skills - Pardede, Parlindungan (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2011)
The notion that the main objective of EFL teaching is to help students to communicate fluently in the target language cause many teachers still believe that an EFL class should focus on mastering linguistic elements only. However, recent trend in EFL teaching indicates the necessity of integrating literature because of its rich potential to provide an authentic model of language use. Among literary genres, short stories seem to be the most suitable choice for this due to its potential to help students enhance the four skills (listening, speaking, reading and writing) more effectively because of the motivational benefit embedded in the stories. The purpose of this article is to familiarize EFL instructors with the effectiveness of using short stories in EFL instruction. After presenting the criteria for selecting a short story, the discussion is focused on how to exploit a short story for enhancing students' language skills.